Implementation of Humanistic Learning Theory in Science and Technology Learning towards Students' Creative Thinking Skills - Damayanti, Devi; Farihah, Umi; Mislikhah, Mislikhah (Education and Sociedad Journal, 2023)
This study addresses the limited application of humanistic learning theory in elementary education, particularly in lower grades, where the teaching and learning process adopts problem-based learning. The research aims to analyze the implementation of IPAS (Integrated Natural and Social Sciences) learning in fostering creative thinking skills, the integration of creative thinking in IPAS learning, and its objectives and benefits. Employing a descriptive qualitative research method, data collection techniques include observation, interviews, and documentation. The findings indicate that while teachers have not fully applied the principles of humanistic learning theory, they prioritize character development by encouraging students to interact effectively with their environment. Additionally, teachers provide learners with opportunities to engage freely in classroom interactions, allowing them to gain meaningful learning experiences and enhance creativity in comprehending the subject matter. The study is expected to contribute to the body of knowledge by highlighting the need to integrate humanistic principles into problem-based learning to foster creative thinking and holistic character development in elementary education.